Corn Nitrogen Fertilization Requirement and Corn–Soybean Productivity with a Rye Cover Crop - Pantoja, Jose L.; Woli, Krishna P.; Sawyer, John E.; Barker, Daniel W. (Soil Science Society of America journal, 2015)
Winter rye (Secale cereale L.) cover crop (RCC) has potential to reduce NO3–N loss from corn (Zea mays L.) and soybean [Glycine max (L.) Merr.] fields. However, RCC effects on annual crop productivity and corn optimal N fertilization requirement are unclear. The objectives were to evaluate corn and soybean yield response to RCC and corn optimal N rate. Treatments were no‐RCC and RCC with six fertilizer N rates (0–225 kg N ha‐1) applied to corn in a no‐till corn–soybean (CS) rotation at four Iowa sites in 2009 through 2011. The RCC biomass and N uptake was low, with a maximum of 1280 kg dry matter (DM) ha‐1 and 26 kg N ha‐1, respectively. In the no‐N control, the RCC reduced soil profile NO3–N by 15 kg N ha‐1 only at time of RCC control before corn planting. Corn canopy sensing, plant height, and plant population indicated more N stress, reduced plant stand, and slower growth with RCC. The RCC reduced corn grain yield by 6% at the economic optimum N rate (EONR). The EONR was the same with no‐RCC and RCC, but plant N uptake efficiency (PUE) was reduced at low N rates with RCC, but not above the EONR. Soybean yield was not affected by RCC. Results indicate N fertilization rate should be the same with or without RCC. Improvement in RCC systems and management could make RCC a more viable practice within no‐till corn and soybean production.